Interaction of the processes of nitrogen and carbon assimilation in soybean plants under the treatment with fungicidal activity substances and the inoculation with nodule bacteria incubated with lectin - Kots, S.Ya.; Kiriziy, D.A.; Pavlyshche, A.V. (Reports of the National Academy of Sciences of Ukraine, 2018)
The relationship between the activity of nitrogen fixation and the photosynthetic rate in soybean plants, which were treated with substances with the fungicidal activity and inoculated with nodule bacteria incubated with lectin is investigated in dynamics. It is shown that the interaction of symbiotic and photosynthetic apparatus of soybean plants gradually increases from the phase of three true leaves to the flowering. It is revealed that the correlation between the photosynthetic rate and the accumulation of dry matter in soybean plants is significant and increases during the vegetation, while the efficiency of the assimilated carbon transformation into a dry substance remains stable. At the same time, the relationship between the nitrogen fixation activity and the accumulation of dry matter weakens.